Prospects of Islamic insurance in India - Syed, Ahmed Salman; Htay, Sheila Nu Nu (Choice College of Arts & Commerce, Pune, 2013)
Life and risk cannot be separated however it can be minimized through insurance. It is the main reason why insurance plays significant role in our daily life. Insurance is a policy between the insured and insurer to provide the benefits in the case of misfortune of the insured. However, from the Islamic perspective, insurance contract contains the prohibited elements such as interest, uncertainty and gambling. This calls for an alternative insurance, i.e. Islamic insurance, suitable for both Muslims and non-Muslims. Many Muslim and non-Muslim countries have introduced Islamic insurance. India is ranked in the third highest Muslim population country after Pakistan and Indonesia. Thus, the potential growth of Islamic insurance is high and this paper highlights the prospects of Islamic insurance in India.